Mechanisms of blood flow restriction training for knee pain: a mini review - Xie, Shi-Yu; Jiang, Xue; Yuan, Jia-Bin; Luo, Jing; Song, Shun; Hu, Hao-Yu (Frontiers in Physiology, 2025)
Knee pain, affecting an estimated 654 million people worldwide, so blood flow restriction training (BFRT) is catching the spotlight as an effective intervention. Evidence continues to demonstrate the effectiveness of BFRT in managing knee pain. However, the mechanism by which BFRT alleviates knee pain remains unclear, thereby limiting its application in clinical pain management. This study aims to elucidate the underlying mechanisms of BFRT to better understand its efficacy in treating knee pain. This review will discuss the influence of muscle hypertrophy, endogenous opioid system, endocannabinoids, inflammation regulation, and conditional pain regulation on BFRT treatment of knee pain. Current studies on BFRT have limitations, such as small sample sizes, relatively low-quality evidence, and lack of mechanistic studies. Therefore, further research on BFRT is needed, particularly high-quality and large-sized randomized controlled trials.